Cellulose‐Nanofiber‐Reinforced Rubber Composites with Resorcinol Resin Prepared by Elastic Kneading. Issue 12 (25th August 2021) - Noguchi, Toru; Bamba, Yasuo; Miura, Takashi; Iwamoto, Rie; Endo, Morinobu; Isogai, Akira
Abstract: A resorcinol resin/water dispersion and a rubber latex are added to 1% 2, 2, 6, 6, ‐tetramethylpyperidine‐1‐oxyl (TEMPO)‐oxidized cellulose nanofibers (TEMPO‐CNFs) dispersed in water, followed by oven drying at 40 °C for 20 h to prepare a dried TEMPO‐CNF/resorcinol resin/latex rubber (DTRL) mixture with a weight ratio of 1/0.5/3. DTRL is then added to a nitrile‐butadiene rubber (NBR) or a carboxy group‐containing NBR (X‐NBR) sheet, and the mixture is kneaded by a two‐roll mill at 20–30 °C with high shear forces. The tensile strength and Young's modulus of the crosslinked DTRL/rubber composite sheets remarkably increased from 10 and 12 MPa, respectively, for the reference sheet to 24 and 82 MPa, respectively, for the DTRL/rubber composite sheets containing ≈10 vol% TEMPO‐CNFs. Scanning electron microscopy revealed that no TEMPO‐CNF agglomerates are present in the DTRL/rubber composite sheets. The tensile properties of the composite sheets are the best when a X‐NBR sheet and NBR latex are used as the matrix rubber and latex in DTRL preparation, respectively. When water‐extracted DTRL (WDTRL, mass recovery ratio ≈94%) is used in place of DTRL, the WDTRL/rubber composite sheets show sufficient water resistance, while the tensile properties are almost the same as those of the DTRL/rubber composite sheets. Abstract : An oven‐dried cellulose nanofiber/resorcinol resin is prepared, and mixed with a rubber sheet by elastic kneading at 20‒30 °C with high shear forces. The tensile strength and Young's modulus of the cellulose nanofiber/resorcinol resin/rubber composite sheets crosslinked remarkably increase with increasing cellulose nanofiber content. Scanning electron microscopy observation shows that no cellulose nanofiber agglomerates are present in the composite sheets.